The Effect of Current Ratio, Net Profit Margin, Company Size and Assets Structure on Capital Structure in Basic and Chemical Industrial Companies Listed On the Indonesia Stock Exchange for the 2016-2019 Period - Ryan Thamrin; Mariska Sisilia (Enrichment : Journal of Management, 2021)
The basic and chemical industries that are experiencing growth cannot be separated from the capital structure. The purpose of this study was to determine the effect of the current ratio, net profit margin, company size and asset structure on the capital structure of basic and chemical industrial companies listed on the Indonesia Stock Exchange for the 2016-2019 period. A quantitative approach that processes statistical data using multiple linear regression. This type of quantitative research is a causal relationship. The population of this study is 100 basic and chemical industry companies listed on the Indonesia Stock Exchange for the 2016-2019 period.The research sample is 25Company. The result is that the current ratio affects the capital structure of basic and chemical industrial companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The net profit margin has no effect on the capital structure of basic and chemical industrial companies listed on the Indonesia Stock Exchange for the 2016-2019 period. Company size affects the capital structure of basic and chemical industrial companies listed on the Indonesia Stock Exchange for the 2016-2019 period. Asset structure affects the capital structure of basic and chemical industrial companies listed on the Indonesia Stock Exchange for the 2016-2019 period. Current ratio, net profit margin, company size and asset structure affect the capital structure of basic and chemical industrial companies listed on the Indonesia Stock Exchange for the 2016-2019 period.